Mechanistic evidence from classical molecular dynamics and metadynamics revealed the mechanism of resistance to 4-hydroxy tamoxifen in estrogen receptor alpha Y537S mutant. Issue 16 (2nd November 2022) - Bouricha, El Mehdi; Hakmi, Mohammed; Kartti, Souad; Zouaidia, Fouad; Ibrahimi, Azeddine
ABSTRACT: Small molecule antagonists that bind to the ligand-binding domain (LBD) of estrogen receptor alpha (ERα) are effective in treating ERα-positive breast cancer patients. However, acquired treatment resistance is observed in the presence of somatic mutations in LBD of ERα. Y537S is the most aggressive mutation, causing constitutive activity of ERα in the absence of ligand and reducing the affinity and sensitivity of certain antagonists such as 4-hydroxy tamoxifen (4-OHT). To better understand the mechanism of resistance to 4-OHT, we performed a comparative study of wild-type and Y537S mutant ERα in complex with 4-OHT using classical molecular dynamics and metadynamics. The results of this study indicated that Helix 12 (H12) disruption is a typical allosteric effect of 4-OHT, allowing the receptor to maintain an antagonistic conformation. The Y537S mutation induces the loss of this effect by stabilising H12 through the newly formed H-bond between E380 and S537, thereby strengthening H12 to adopt an agonistic conformation even when 4-OHT is bound. The obtained results and the approaches applied in this study could be used as proof of principle for discovering more potent ERα inhibitors to overcome the endocrine resistance.